Unexpected reduction-allylic oxidation of hemisynthetic diosphenols from longipinene derivatives. (October 2020) - Chacón-Morales, Pablo A.; Santiago-Dugarte, Carolina; Amaro-Luis, Juan M.
Graphical abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered. Highlights: Compound 1 was obtained by basic hydrolysis of a CH2 Cl2 extract from S. lucida . Were described the procedure to obtain and elucidate six oxidation products (2-7 ) from 1 . Compounds 2, 3, 5 and 7 are diosphenolic derivatives. Compounds 4 and 6 experimented unexpected allylic oxidations and reductions. Reaction mechanism to explain the allylic oxidations and reductions were proposed. Abstract: The 7β, 9α-dihydroxylongipin-2-en-1-one (1 ) was obtained by basic hydrolysis of a dichloromethane extract of the resinous exudate from aerial parts of Stevia lucida . The treatment of 1 with potassium permanganate in concentrated hydrochloric acid generated two diosphenolic derivatives (2 and 3 ) one of which showed an unexpected allylic oxidation (2 ). Diosphenol 3 was treated with Jones reagent yielding four oxidation products (4 -7 ). Two of these (4 and 6 ) have structural changes that suggest a process of reduction of the enolic double bond of diosphenol and another process of allylic oxidation. To explain the formation of the compounds 4 and 6 a plausible reaction mechanism based on a sequence of isomerizations was proposed. The structures of (1 -7 ) were established based on NMR (1D and 2D) data interpretation.